Cloud based computational intelligence approaches to machine learning and big data analytics: literature survey - Venkata Siva Reddy, D; Vasanth Kumar Mehta, R (International Journal of Engineering and Technology, 2018)
Today there are many sources through which we can access information from internet and based on the dependency now there is an over flow of data either in refined form or unrefined form. Handling large information is a complicated task. It has to overcome many challenges. There are some challenges like drawing useful information from undefined patterns which we can overcome by using data mining techniques but certain challenges like scalability, easy accessing of large data, time, or cost areto be handled in better sense.Machine learning helps in learning patterns from data automatically and can be leverage this data in further predictions. Cloud computing has now turned out to be a big alternative while handling big data because cloud itself carry certain features which help in analyzing and accessing big data in proper manner.Before switching to Cloud based approaches it provides an ease of set up or testing and is economical.Thus there is a demand for cloud computing and machine learning techniques with Hadoop or Spark.Mainly we are focusing on various works that have been done in handling big data. Here the analysis of various algorithms that are used by various researches in handling big data as well as outcome that they obtained in overcoming the challenges in handling big data.